Monitoring the Impacts of Wildfires on Forest Ecosystems and Public Health in the Exo-Urban Environment Using High-Resolution Satellite Aerosol Products from the Visible Infrared Imaging Radiometer Suite (VIIRS) - Amy K. Huff; Shobha Kondragunta; Hai Zhang; Raymond M. Hoff (SAGE Publishing, 2015)
Increasing development of exo-urban environments and the spread of urbanization into forested areas is making humans and forest ecosystems more susceptible to the risks associated with wildfires. Larger and more damaging wildfires are having a negative impact on forest ecosystem services, and smoke from wildfires adversely affects the public health of people living in exo-urban environments. Satellite aerosol measurements are valuable tools that can track the evolution of wildfires and monitor the transport of smoke plumes. Operational users, such as air quality forecasters and fire management officials, can use satellite observations to complement ground-based and aircraft measurements of wildfire activity. To date, wildfire applications of satellite aerosol products, such as aerosol optical depth (AOD), have been limited by the relatively coarse resolution of available AOD data. However, the new Visible Infrared Imaging Radiometer Suite (VIIRS) instrument on the Suomi National Polar-orbiting Partnership (S-NPP) satellite has high-resolution AOD that is ideally suited to monitoring wildfire impacts on the exo-urban scale. Two AOD products are available from VIIRS: the 750-m × 750-m nadir resolution Intermediate Product (IP) and the 6-km × 6-km resolution Environmental Data Record product, which is aggregated from IP measurements. True color (red, green, and blue [RGB]) imagery and a smoke mask at 750-m × 750-m resolution are also available from VIIRS as decision aids for wildfire applications; they serve as counterparts to AOD measurements by providing visible information about areas of smoke in the atmosphere. To meet the needs of operational users, who do not have time to process raw data files and need access to VIIRS products in near-real time (NRT), VIIRS AOD and RGB NRT imagery are available from the Infusing satellite Data into Environmental Applications (IDEA) web site. A key feature of IDEA is an interactive visualization tool that allows users to display tailored combinations of AOD and RGB imagery, as well as overlay the VIIRS smoke mask and fire hotspots at pixel resolution (~750-m × 750-m), and zoom into the county level. Two case studies of recent wildfires in the Western US are presented to show how operational users can access and display VIIRS aerosol products to monitor the transport of smoke plumes and evolution of fires in the exo-urban environment on the regional and county scales. The new National Oceanic and Atmospheric Administration (NOAA) Western Region Fire and Smoke Initiative is also discussed, which will enhance IDEA to allow visualization of VIIRS aerosol products down to the neighborhood scale. The new high-resolution VIIRS aerosol products can be used for NRT monitoring of human exposure to smoke, and they can be used to gauge the spread of fires and, thus, provide advanced warning for evacuations and fire suppression efforts, thereby reducing risks to human populations and forest ecosystems in the exo-urban environment.